0490 Insomnia Among Military Members With Osa. (12th April 2019) - Foster, Brian; Kravitz, Shena; collen, jacob; holley, aaron
Abstract: Introduction: Obstructive sleep apnea is more prevalent in military members than civilian counterparts despite a younger and thinner population. CPAP adherence among military members is often suboptimal, raising concerns about how effectively this population is evaluated and treated with regards to OSA phenotype. The purpose of our study was to evaluate the prevalence of the low arousal threshold (LAT) phenotype among military patients with OSA and describe the relationship with comorbid insomnia. Methods: Retrospective review of consecutive service members found to have OSA following level one attended nocturnal polysomnography from 2012-2014 performed for clinical suspicion of sleep-disordered breathing. Low arousal threshold (LAT) was based on previously published non-invasive PSG criteria (AHI<30 events/hour, oxygen saturation nadir>82.5% and >58.3% of events are hypopneas). Clinic intake questionnaire including the Insomnia Severity Index (ISI) and the electronic medical record data were reviewed for all patients. Results: 308 patients were evaluated (87.3% male, age 41.0±8.8, BMI 28.9±4.3 kg/m2, AHI 11.9±11.4 events/hour). The mean ISI score was 12.1±5.5, consistent with subthreshold insomnia, and 38.2% of patients met criteria for clinical insomnia (ISI>14). The majority of the cohort met criteria for LAT (n=278 (90.3%)). Patients with an LAT had a higher ISI score (12.0±5.0 v 10.0±5.0, p=0.05), and the mean percentage of hypopneas varied significantly across ISI categories (p=0.02). Diagnoses of PTSD and TBI did not predict the occurrence of the LAT. Conclusion: The majority of service members with OSA fulfill PSG criteria for LAT. Symptoms of insomnia are more prevalent among patients with an LAT, and the mean percentage of hypopneas is related to ISI categorization. Further research is needed to clarify the interactions between comorbid insomnia, the LAT, and OSA. Support (If Any): N/A